Apology Strategies on Characters’ Utterances in Moana and Moana 2 Movies - Karundeng, Grace Natasha; Pradipta, Bramantya (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study analyzes apology strategies used by characters in the Moana and Moana 2 animated movies. The study aims to find the types of apology strategies in the characters’ utterances and to determine which strategy is most frequently used. The theory of apology strategies by Olshtain and Cohen (1983), which includes five main types: an expression of apology, an explanation or account, an acknowledgment of responsibility, an offer of repair, and a promise of forbearance was applied in this research. This research used a descriptive qualitative method. The results show that a total of 53 utterances contain apology strategies. Among them, an explanation or account was the most frequently used strategy, followed by acknowledgment of responsibility, expression of apology, offer of repair, and promise of forbearance. These findings reveal that characters tend to provide reasons or explanations as a way to express regret and maintain harmony in their interpersonal communication. The study contributes to the understanding of apology strategies in animated movies and how they reflect real-life communication behavior.